Application of Good Corporate Governance (GCG) Principles in Cirebon Publications According to Islamic Economics - Tamamiyah, Lutfiyatut; Dwi Putri Pramesti, Ginna Novarianti (CV. Publikasi Indonesia, 2024)
Recent developments show that it is not enough for management to ensure that the leadership management process is effective. In order for management to run well, a new tool is needed, namely Good Corporate Governance (GCG). This concept emphasizes two things, first, the importance of shareholders' rights to obtain accurate and timely information, and second, the company's obligation to publish all information regarding company performance accurately, timely and transparently. property and interested parties. The study aims to evaluate the extent to which the principles of good corporate governance (GCG) have been implemented in the Indonesian banking sector, both in conventional and Islamic banks. In this study, the type of research used is a type of qualitative descriptive research. The results of various national and international independent research institutions show that Indonesian business people do not understand the importance and strategic implementation of GCG principles. In addition, organizational culture also influences the implementation of GCG in Indonesia.